Lipid Accumulation Product (LAP) Index as Predictor Tool for Metabolic Syndrome - Pathan , Md Faruque (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not available J Bangladesh Coll Phys Surg 2022; 40: 1-2